A Self-Adjusting Spectral Conjugate Gradient Method for Large-Scale Unconstrained Optimization. (11th April 2013) - Qiu, Yuanying; Cui, Dandan; Xue, Wei; Yu, Gaohang
Abstract : This paper presents a hybrid spectral conjugate gradient method for large-scale unconstrained optimization, which possesses a self-adjusting property. Under the standard Wolfe conditions, its global convergence result is established. Preliminary numerical results are reported on a set of large-scale problems in CUTEr to show the convergence and efficiency of the proposed method.